1996
DOI: 10.1021/tx9502047
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal Catalyzed N-Hydroxylation of Guanabenz and Reduction of the N-Hydroxylated Metabolite:  Characterization of the Two Reactions and Genotoxic Potential of Guanoxabenz1

Abstract: The N-reduction of the centrally acting alpha 2-adrenoreceptor agonist guanoxabenz (Benzérial), an N-hydroxyamidinohydrazone, to the amidinohydrazone guanabenz (Wytensin, Hipten, Rexitene) by microsomal fractions from rabbits, pigs and humans has been detected in vitro. The conversion rates with rabbit microsomal fractions were markedly slower than those in the cases of fractions from humans and pigs. It was also possible to demonstrate the N-oxidation of guanabenz to guanoxabenz by the use of microsomal fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…The reduction of other N-oxygenated basic nitrogen-containing functional groups by these liver preparations has also been described for N-hydroxylated guanidine, N-hydroxydebrisoquine (12), and amidinohydrazone guanoxabenz (30). Previous studies (4, 7) have also shown that liver microsomal preparations can also catalyze NADPH-dependent N-hydroxylation of these compounds, but the rates of N-hydroxylation were about 2 orders of magnitude lower than rates of reduction, which suggests that the latter reaction may prevent accumulation of toxic N-hydroxylated products.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The reduction of other N-oxygenated basic nitrogen-containing functional groups by these liver preparations has also been described for N-hydroxylated guanidine, N-hydroxydebrisoquine (12), and amidinohydrazone guanoxabenz (30). Previous studies (4, 7) have also shown that liver microsomal preparations can also catalyze NADPH-dependent N-hydroxylation of these compounds, but the rates of N-hydroxylation were about 2 orders of magnitude lower than rates of reduction, which suggests that the latter reaction may prevent accumulation of toxic N-hydroxylated products.…”
Section: Discussionmentioning
confidence: 92%
“…Thus an amidoxime group can serve as a prodrug functionality for an amidino group. The same concept can be applied to guanidines and amidinohydrazones and their N-oxygenated derivatives (12,30). Therefore, strong basic nitrogen-containing functional groups, which are protonated under physiological conditions and are not absorbed as cations, can be made orally available by introducing a hydroxy group, which lowers the pK a values significantly.…”
Section: Met Ile Leu His Pro Asp Val Gln Arg Arg Val Gln Gln Glu Ile Aspmentioning
confidence: 99%
“…Prior consent of the local medical ethics committee and from the donors was obtained for these studies. Human and pig microsomes from liver were obtained by ultracentrifugation as described previously (Clement et al, 1996). The kidney microsomes were prepared analogously.…”
Section: Methodsmentioning
confidence: 99%
“…Our study shows that XO mediates the N-reduction of guanoxabenz with a K m value in the micromolar range (65.2 Ϯ 4.5 µM with NADH and 39.0 Ϯ7.1 µM with xanthine as electron donor). Interestingly, Clement et al [31] have reported that rabbit microsomes can also catalyze N-reduction of guanoxabenz in the presence of NADH, the K m value for the reaction being about 34 µM. Moreover, these authors reported recently that the microsomal N-reduction is catalyzed by an enzyme system composed of cytochrome b 5 , NADH cytochrome b 5 -reductase and benzamidoxime reductase [32].…”
Section: Discussionmentioning
confidence: 99%